2016
DOI: 10.1242/dmm.025668
|View full text |Cite
|
Sign up to set email alerts
|

A chemical with proven clinical safety restores Down syndrome-related phenotypes via DYRK1A inhibition

Abstract: DYRK1A is important in neuronal development and function, and its excessive activity is considered a significant pathogenic factor in Down syndrome and Alzheimer's disease. Thus, inhibition of DYRK1A has been suggested to be a new strategy to modify the disease. Very few compounds, however, have been reported to act as inhibitors, and their potential clinical uses require further evaluation. Here, we newly identify CX-4945, the safety of which has been already proven in the clinical setting, as a potent inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 43 publications
4
84
0
Order By: Relevance
“…Apart from our own focus on CLK2 as a molecular target for the treatment of autistic features in PMDS patients with SHANK3 deletions, various research groups have suggested functional modulation of the closely related kinase Dyrk1A as a potential therapeutic modality in addressing the cognitive and behavioral deficits in Down syndrome . We hope that this work may prove helpful in the development of ATP‐competitive Dyrk1A inhibitors, with the likely required selectivity over CLK1, ‐2, and ‐4, which are associated with adverse genotoxic potential.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Apart from our own focus on CLK2 as a molecular target for the treatment of autistic features in PMDS patients with SHANK3 deletions, various research groups have suggested functional modulation of the closely related kinase Dyrk1A as a potential therapeutic modality in addressing the cognitive and behavioral deficits in Down syndrome . We hope that this work may prove helpful in the development of ATP‐competitive Dyrk1A inhibitors, with the likely required selectivity over CLK1, ‐2, and ‐4, which are associated with adverse genotoxic potential.…”
Section: Resultsmentioning
confidence: 95%
“…Two publications on CX‐4945 by Kim et al. described this compound in its role as a highly potent CLK inhibitor, and in its role as a highly potent Dyrk1A inhibitor; Dyrk1A inhibition is proposed to be a potential treatment for Down syndrome . The high potency of CLK inhibitor Cpd‐2 is described by Araki et al .…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, several new molecules that inhibit DYRK1A activity have been proven to reduce some AD phenotypes such as tau expression or phosphorylation, APP levels or Aβ load (Kim et al, 2016;Abbassy et al, 2015;Contadeur et al, 2015). Future studies should test the efficacy of the only DYRK1A inhibitor that has been so far tested in humans, epigallocatechin-gallate (EGCG) (De la Torre et al, 2014; to prevent different AD-associated alterations.…”
Section: Resultsmentioning
confidence: 99%
“…In this proof‐of‐concept study, we report that Dyrk1 is a valid new target for AD treatment and show that its chronic inhibition reduced Aβ and tau pathology and ameliorated cognitive deficits in 3xTg‐AD mice. These data are consistent with previous results indicating that CX‐4945, a selective and potent Dyrk1a inhibitor, reduces tau pathology in multiple systems (Kim et al ., ). Taken together these results clearly indicate that Dyrk1 represents a valid therapeutic target for AD and support the development of new, effective, and clinically safe compounds aimed at reducing Dyrk1 activity.…”
Section: Discussionmentioning
confidence: 97%